Pelayanan Perekaman Kartu Tanda Penduduk Elektronik di Kantor Kecamatan Kanor (Studi Tentang kualitas Pelayanan Publik) - Suprastiyo, Ahmad (Universitas Serang Raya, 2018)
Improving the quality of public services is an important concern for the government, this is evidenced by the enactment of Law Number 25 of 2009 concerning Public Services. The recording service for electronic resident identification cards is an administrative service provided by the government to its citizens. However, the reality in the field of electronic ID card recording service at Kanor District Office is not in accordance with the expectations of the community in obtaining public services, this can be explained from the lack of service speed, courtesy and friendliness of service personnel, implementing competence, and facilities and infrastructure in the service room. This study aims to find out and explain the service of recording electronic identity cards in the Kanor sub-district office (study of the quality of public service). The approach mix method in which qualitative data generalised through whislt quantitative data. Determination of informants using purposive snowball sampling. Data analysis uses data collection, data reduction, data display, and conclusion drawing / verifying. The results showed that the service quality of electronic resident card recording at the District Office of Kanor was from the aspect of infrastructure and facilities, implementing competence and good implementation behavior, but from the aspect of slow service time (not good).